Peningkatan Hasil Belajar Pada Pembelajaran Tematik Terpadu Menggunakan Model Inkuiri di S - Nengsih Kamala Sari; Zaiyasni Zaiyasni (Universitas Negeri Padang, 2020)
The aims of the This study aims to describe the application of the inquiry learning model, to improve learning outcomes in integrated thematic learning in class V SDN 07 Belakang Balok Bukittinggi. This type of research is classroom action research (CAR). Using qualitative and quantitative approaches. The subjects in this study were the teacher and 38 students in class V SDN 07 Belakang Balok Bukittinggi. The results showed an improvement. In the first cycle, the planning observation results were 79.16% (B) increased in the second cycle to 94.4% (A). The results of observations of aspects of the teacher cycle I, 79.6% (B) increased in cycle II, 90.6%. The results of the observation of student aspects in the first cycle, 78.1% (B) increased in the second cycle to 90.6% (A). The average assessment of student learning outcomes in the first cycle at the knowledge value of 77.7 increased in the second cycle to 89.8, while in the first cycle of skills assessment, 72.6 (B) increased in the second cycle to 89.01.